Sistemas Holomorfos - Silva, Carlos Vinícius das Neves [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Neste trabalho estudaremos propriedades locais e globais de equações diferenciais complexas de primeira ordem. Classificaremos o retrato de fase no disco de Poincaré de uma família de equações racionais e por fim, estudaremos sistemas holomorfos por partes em especial, apresentaremos condições que garantem a existência de ciclo limite para estes sistemas.

In this work we will study local and global properties of complex first order differential equations . We will classify the phase portraits on the Poincaré disk of a family of rational equations and finally, we will study piecewide holomorphic systems, in particular we provide conditions to ensure the existence of limit cycles of these systems.
Holomorphic systems
Keywords: Sistemas holomorfos; Sistemas holomorfos por partes; Sistemas de Filippov; Holomorphic systems; Piecewide holomorphic systems; Filippov systems